Reflection of a personality’s experience and perception of life events in oral and written narrations - Kresan, O.; Shulga, T. (My University, 2019)
The article is devoted to the study of peculiarities of a personality’s life events experience and perception in oral and written narrations. The author analyses views of leading researchers on peculiarities of oral and written speech, which reflect consciousness processes and personality’s inner world. The results of empirical research into oral and written narrations about life events were presented. The fea tures and conditions of experience and perception of life events in the narrative were defined. As a result of the empirical research it has been proved that it is on the above mentioned conditions and features that experience and perception of life events in the narration largely depend on, rather than its form – oral or written. The peculiarities of reflection of a personality’s life events experience and perception in oral and written narrations are summarized.
Keywords: life event; experience; perception; narrative; narration